Implementation of the International Convention On The Elimination Of All Forms Of Racial Discrimination In Uzbekistan: Problems And Prospects - Rakhimova Muattara.Abdusattarovna (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article examines the implementation of the International Convention on the Elimination of All Forms of Racial Discrimination (CERD) in the Republic of Uzbekistan, focusing on the existing legal framework, institutional mechanisms, and challenges to effective realization. The study analyzes constitutional guarantees and national legislation adopted to promote equality and protect the rights of ethnic minorities. Despite notable progress—including the adoption of the 2023 Constitution and the development of state policy in interethnic relations—systemic challenges remain, such as insufficient public awareness, limited data collection, and the need for stronger law enforcement mechanisms. The article concludes with recommendations for enhancing national implementation of CERD through educational reforms, improved data monitoring, and international cooperation.